(untitled) (INTERNATIONAL SCIENTIFIC AND PRACTICAL E-CONFERENCE " MODERN TENDENCIES OF DIGITAL EDUCATION AND WAYS OF IMPLEMENTING THEM IN THE EDUCATIONAL PROCESS" – Brno, Czech, 2024)
There are words in the Uzbek language that can perform different tasks in different contexts, have multiple meanings, homonyms, or terminological meaning. It is clear that all their meanings are not reflected in the explanatory dictionary, because terminological, encyclopedic, or explanation of names is not part of the task of an explanatory dictionary. Therefore, an annotated dictionary is not enough to collect all such explanations of a certain lexical unit. For this purpose, it is required to integrate the information in different types of dictionaries, where such units are involved.